Effect of clinical endometritis on physiological, hematological, biochemical and endocrinological profiles in crossbred cows under tropical island ecosystem - PERUMAL, P; CHAURASIA, D; DE, A K; BHATTACHARYA, D; SUNDER, JAI; BHOWMICK, SNEHA; KUNDU, A; MISHRA, P C (The Indian Journal of Animal Sciences, 2021)
The present study was carried out to assess the effect of endometritis on hematological, physiological, antioxidant, oxidative and endocrinological profiles in crossbred cows under tropical island ecosystem of Andaman and Nicobar Islands. Each 12 number of cows affected with clinical endometritis was selected as group 2 and without endometritis as group 1. These cows were in same parity in same locality with similar type management. Physiological profiles, hematological profiles, antioxidant profiles and hormone profiles were estimated. The result revealed that the crossbred cows with endometritis were suffering severe anaemia. The endometritis affected animals were shown significantly low level of antioxidant profiles and higher MDA level than the unaffected animal groups. Similarly endocrinological profiles revealed that the endometritis affected animals have significantly higher level of CORT and lower level of E2, P4, FSH, LH and T4 than the unaffected crossbred cows. It was concluded that the endometritis was due to anaemia, lack of antioxidants, over production of free radicals and disturbances of endocrinological profiles in crossbred cows of Andaman and Nicobar Islands.